Inductive reasoning, domain specific and complex problem solving: relations and development - Molnár, Gyöngyvér; Greiff, Samuel; Csapó, Benő (Thinking skills and creativity, 2013)
This paper focuses on three different types of reasoning: domain-specific problem solving, complex (general) problem solving, and inductive reasoning. The objective of the study is to examine the differences in the developmental levels of inductive reasoning, domain-specific problem solving, and complex problem solving between three age groups and to describe the relations between the three constructs. The sample was drawn from 3rd to 11th grade students (aged 9-17) in Hungarian primary and secondary schools. There were 300-400 students in each cohort. The internal consistencies of the tests were good: Chronbach α varied between .72 and .95. Each of the skills showed a developmental tendency that could be identified with a logistic curve. In every area the pace of development proved to be relatively slow and the steepest change took place in Grade 7. The bivariate correlations between the three constructs were moderate ranging from .35 to .44 signalling that they do not constitute the same construct. The strength of the relationships between inductive reasoning and complex problem solving proved to be the most stable over time. The correlations between domain-specific and complex problem solving showed an increasing trend over time indicating that the strategies used in different problem solving situations become more similar with age. This study provides evidence that inductive reasoning, domain-specific problem solving and complex problem solving are related but distinct constructs and these skills can be fostered most efficiently between Grades 6 and 8.